Implementasi Qanun No. 7 Tahun 2016 dalam Upaya Restorasi di Desa Tenggulun, Aceh Tamiang - Aang Kunaifi; Nina Siti Salmaniah Siregar; Budi Hartono (Mahesa Research Center, 2023)
This study aims to determine the Implementation of Qanun No. 7 of 2016 concerning Aceh Forestry in Restoration Efforts in Tenggulun Village, Aceh Tamiang and the factors that influence the implementation referred to in the Aceh KPH Region III Office in Langsa City. The method used is descriptive qualitative with data collection carried out through observation, interviews and documentation. While the data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the research it is known that the Implementation of Qanun No. 7 of 2016 concerning Aceh Forestry in Restoration Efforts in Tenggulun Village Aceh Tamiang In preventing damage and restoring the function of forest areas in the Working Area of KPH Region III Aceh has been carried out in accordance with the provisions of laws and regulations, in this case the provisions Law No. 11 concerning the Aceh government and its derivative Qanun No. 7 of 2016 concerning Aceh Forestry. Communication, resources, and bureaucratic structure have been going well, but in its implementation, there is still no Standard Operating Procedures (SOP). In terms of fragmentation, there is no significant distortion. While those that support implementation are dispositions that are influenced by the main tasks and functions in accordance with the provisions of the Governor of Aceh Regulation, organizational culture factors, incentives. In the event that there are still constraints in KPH Region III Aceh.